Applications of M2ZrO2 (M = Li, Na, K) composite as a catalyst for biodiesel production. (15th February 2021) - Dai, Yong-Ming; Li, Yan-Yun; Lin, Jia-Hao; Kao, I.-Hsiang; Lin, Yu-Jun; Chen, Chiing-Chang
Abstract: Biodiesel is nontoxic and produces little pollution during combustion. It can be used alone or mixed with petroleum diesel as an additive and is a potential alternative fuel. We investigated the use of zirconium dioxide and three alkali metals (Li, Na, and K) for M2 ZrO2 (M = Li, Na, K) composites as solid base catalysts for biodiesel production. M2 ZrO2 catalysts were prepared using a simple solid-state reaction and by mixing and grinding zirconium dioxide with alkali metals that were calcined at 800 °C in the air for 4 h. The properties of the catalyst were characterized by Field Emission Scanning Electron Microscope (FE-SEM), Brunauer-Emmett-Teller (BET), X-Ray powder diffractometer (XRD), Fourrier Transform Infrared Spectroscopy (FT-IR) and Hammett indicator method, and analyzed the composition of biodiesel by Gas chromatography. The optimum conditions for the process were a Li2 ZrO2 calcination temperature of 800 °C for 4 h, a catalyst amount of 6 wt%, a methanol to oil molar ratio of 8:1, and a reaction temperature of 65 °C. The process could transesterify oil into methyl esters at a 98%–99% conversion rate in 2 h for all series. A series of transesterification experiments was conducted to identify the proper operating conditions. The final product met the selected biodiesel fuel properties in accordance with ASTM D6751.